A dual-reporter LDLR system integrating fluorescence and luminescence for understanding LDLR regulation and facilitating drug discovery - Jiao, Peng; Yang, Na; Jia, Qianfeng; Fan, Baozhen; Feng, Ke; Yu, Jian; Zhao, Shengtian (Frontiers in Molecular Biosciences, 2025)
IntroductionThe low-density lipoprotein receptor (LDLR) is integral to cholesterol metabolism and cardiovascular health. Enhancing LDLR expression is a promising strategy for treating hyperlipidemia and reducing the risk of atherosclerosis. However, current LDLR reporter systems have limitations in detecting both transcriptional and translational regulation. To address this, we developed a novel dual-reporter LDLR system incorporating Enhanced Green Fluorescent Protein (EGFP) and Gaussia luciferase (Gluc) to enable precise monitoring of LDLR expression and function.MethodsA CRISPR/Cas9-mediated knock-in strategy was used to integrate EGFP and Gluc upstream of the stop codon located in exon 18 of the LDLR gene in HEK293 cells. The dual-reporter system allows real-time visualization of LDLR expression via EGFP fluorescence and quantitative assessment through secreted Gluc activity. The system was validated using western blotting, immunofluorescence, and functional assays, including DiI-LDL uptake and drug response analyses with statins and PCSK9 inhibitors.ResultsThe established LDLR-EGFP-Gluc knock-in cell line faithfully recapitulates endogenous LDLR expression and function. EGFP fluorescence accurately reflects LDLR expression dynamics, while Gluc activity provides a highly sensitive and quantitative readout. Functional assays confirmed that LDLR expression responds appropriately to statins and PCSK9 inhibitors. Additionally, screening for transcriptional regulators identified FOXP3 and CREB as novel modulators of LDLR expression, with CREB-mediated regulation involving the sterol regulatory element-binding protein 2 (SREBP2) pathway.DiscussionThis dual-reporter system enables complementary monitoring of LDLR dynamics, providing enhanced sensitivity, accuracy, and versatility for studying LDLR regulation and function, as well as facilitating drug discovery targeting hyperlipidemia and cardiovascular diseases.